2018
DOI: 10.1021/acs.chemrestox.8b00219
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Kidney Metabolism in Rats after Subchronic Combined Exposure to Low-Dose Cadmium and Chlorpyrifos

Abstract: Cadmium (Cd) and chlorpyrifos (CPF) often coexist in the environment and induce combined toxicity to organisms. Here we studied the combined nephrotoxicity of environmentally relevant low doses of Cd and CPF. We treated the mice for 90 days with different doses of Cd and CPF and their mixtures via oral gavage. Then histopathological evaluation and biochemical analysis for kidney tissues were carried out. The change of metabolites in kidney was detected by using a metabolomics approach using GC-MS. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…A large number of metabolomic studies have employed animal models or cell lines to study the toxicity of different pesticides. , In recent years, metabolomics has also been applied to study the effect of OP, PYR, or OC pesticide exposure. For example, a cross-sectional study of 83 pregnant women characterizing the urine metabolome found that pesticide mixtures increased oxidative stress and disturbed energy metabolism, while a larger study of 750 pregnant women identified mitochondrial catabolic pathways as being associated with low-level exposure to OCs .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of metabolomic studies have employed animal models or cell lines to study the toxicity of different pesticides. , In recent years, metabolomics has also been applied to study the effect of OP, PYR, or OC pesticide exposure. For example, a cross-sectional study of 83 pregnant women characterizing the urine metabolome found that pesticide mixtures increased oxidative stress and disturbed energy metabolism, while a larger study of 750 pregnant women identified mitochondrial catabolic pathways as being associated with low-level exposure to OCs .…”
Section: Introductionmentioning
confidence: 99%
“…The abuse of Chl could cause environmental pollution including water contamination, soil degradation, accumulation in crops and potential risk to animals [1 − 3]. Besides, exposure to Chl also has great threat to human health, such as affect male reproduction [4], neurotoxicity [5], nephrotoxicity [6], induce the proliferation of breast cancer cells [7,8] and acute toxicity [9]. Thus, the toxicity of Chl to environment and humans lead to urgently exploit sensitive, simple, low cost and on-site rapid methods for Chl analysis and detection, since the instrumental techniques (high performance liquid chromatography [10,11], gas chromatography [12], mass spectrometry [13], surface enhanced Raman scattering [14], etc.)…”
Section: Discussionmentioning
confidence: 99%
“…For histopathological analysis, the kidney and liver tissues of the rats were dissected immediately at the end of the 90-day exposure to the pesticide, and then were fixed in a solution of 10% formalin. After fixation, the specimens were dehydrated with 80, 95, 100% gradient alcohol, and then soaked in melted wax, and finally embedded in paraffin [ 25 ]. After that, the paraffin blocks were cut into 4-μm-thickness sections using a microtome (Microm HM 340E, Thermo Fisher Scientific, USA), then were stained with hematoxylin and eosin.…”
Section: Methodsmentioning
confidence: 99%